2009
DOI: 10.1186/1471-2334-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Poor concordance between interferon-γ release assays and tuberculin skin tests in diagnosis of latent tuberculosis infection among HIV-infected individuals

Abstract: BackgroundA new generation of diagnostic tests, the interferon-γ release assays (IGRAs), have been developed for the detection of latent tuberculosis infection (LTBI). Limited data are available on their use in HIV-infected persons.MethodsA cross-sectional study was carried out at 2 HIV clinics in Atlanta to assess the utility of two IGRA tests (T-SPOT.TB [TSPOT] and QuantiFERON-TB Gold in Tube [QFT-3G]) compared to the tuberculin skin test (TST).Results336 HIV-infected persons were enrolled. Median CD4 count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
7
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 20 publications
(31 reference statements)
11
71
7
4
Order By: Relevance
“…However, TST reactivity to BCG has also been demonstrated long after the period that the effect of the BCG vaccination is expected to have waned off 20 , which may explain why our study found more LTBI among adolescents who had a BCG scar (BCG vaccination). Though the demonstration of TST reactivity to BCG vaccination creates controversy about the use of TST to measure LTBI in countries with high BCG coverage, such as Uganda 21,22 , studies that used interferon gamma release assays (IGRA's), that are believed not to be affected by BCG have shown no added value in estimation of LTBI in high BCG vaccination areas 7,8,22 .…”
Section: Risk Factors Of Latent Tb Infectionmentioning
confidence: 99%
“…However, TST reactivity to BCG has also been demonstrated long after the period that the effect of the BCG vaccination is expected to have waned off 20 , which may explain why our study found more LTBI among adolescents who had a BCG scar (BCG vaccination). Though the demonstration of TST reactivity to BCG vaccination creates controversy about the use of TST to measure LTBI in countries with high BCG coverage, such as Uganda 21,22 , studies that used interferon gamma release assays (IGRA's), that are believed not to be affected by BCG have shown no added value in estimation of LTBI in high BCG vaccination areas 7,8,22 .…”
Section: Risk Factors Of Latent Tb Infectionmentioning
confidence: 99%
“…Yine HIV pozitif hastalarda IGRA ve TCT'nin karşılaştırıldığı çalışmalarda pozitiflik oranında bir fark saptanmamıştır [27][28][29][30] .…”
Section: Discussionunclassified
“…39 However some studies have shown that IGRAs (particularly the TBSPOT.TB assay) might be more sensitive than the TST in detecting latent TB infection in people who are HIV infected with severe immune suppression. [40][41][42][43][44][45][46][47] A study in South Africa demonstrated that patients with very low CD4 counts who had recently been treated for active TB had high rates of response using the TSPOT.TB test. This study suggested that the TSPOT.TB has utility even in a population that had a mean CD4 + T-cell count of 98.…”
Section: Discussionmentioning
confidence: 99%